Effect of Short-Term Extra Maltodextrin during a Diet Break on the Resistance Training Performance of Rattus norvegicus - Indiarto, Muhammad Irfan; Irwadi, Irfiansyah; Lukitasari, Lina; , Atika (Folia Medica Indonesiana, 2023)
Highlights: 1. The ongoing advancement of dietary research has significant importance in the exploration of strategies to optimize the impact of nutrition on performance during resistance training. 2. This study provides a prompt for future research to explore the effectiveness of incorporating an additional dietary strategy that may enhance resistance training performance. Abstract: Poor diet with a purpose to lose a certain body weight or body fat can impair muscle protein synthesis. This results in muscle loss and poor performance in physical training, particularly resistance training. This study aimed to determine the short-term effect of extra carbohydrates, specifically in the form of maltodextrin, during a diet break on the resistance training performanced by rats. This study was an experimental laboratory study with a randomized posttest-only control group design. Twenty-seven male rats, aged 3 months with a weight range of 140–165 g, were randomly and equally assigned into three groups: KN (standard diet), KP (75% calorie intake), and K1 (65% calorie intake with a diet break and extra maltodextrin every week). These diets were administered for four weeks, during which the rats had ad libitum feeding. Additionally, the rats underwent ladder-climbing training three times a week. The body weight was measured pre- and post-treatment, while the performance in resistance training was evaluated post-intervention using a ladder climbing platform. There was no significant difference in the weight before and after treatment, with p>0.05 for the increments (âˆ†) among KN (14.00±9.89 g), KP (13±9.5 g), and K1 (20.89±14.77 g). According to the posttest assessment results, only 17 out of 27 rats succeeded in the maximum weightlifting test. This study showed that a short-term high-carbohydrate diet break does not improve the resistance training performance of rats. Further research is necessary to ascertain the outcomes of the treatment implemented over an extended period of time.